Co-movement of interest rates in Hong Kong and Singapore money markets - Zhang, Rongxia (2008)
The rapid development and globalization in world financial markets have prompted much research in the area of financial market integration. Most of these studies focus on the international linkages of real interest rates. The intent of this study is to investigate the extent to which Hong Kong and Singapore monetary markets are integrated by analyzing the co-movement of interest rates in the two money markets.